The Principles of Istifham in Surah Al-Balad: A Stylistic Study of the Rhetoric of Kalam Insya’i - Zahro, Mahdiya Intan (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research aims to analyze the use of uslub istifham in Surah Al-Balad through a balaghah stylistic approach in order to reveal the rhetorical function of kalam insha’i in the Al-Qur’an. This research focuses on verses 5, 7, 8, and 12 using a qualitative-descriptive method based on text analysis supported by classical balaghah theory. This approach allows a deeper understanding of the implicit meaning behind the interrogative structure as well as its contextual significance in the surah, both from linguistic and rhetorical aspects. The research results show that the form of istifham in verses 5 and 7 functions as inkari (denial), which aims to refute human arrogance and the assumption that he is not under Divine power and supervision. In verse 8, istifham functions as a taqrir (affirmation), which emphasizes Allah’s blessings and encourages implicit recognition from humans. Meanwhile, verse 12 demonstrates the function of ta’zim (glorification), which aims to elevate the meaning of "al-’aqabah" and draw the reader’s attention to its profound and complex significance. These variations demonstrate that the istifham method plays a crucial role in building rhetorical intensity, guiding the reader’s reflection, and persuasively reinforcing moral and spiritual messages. Therefore, this study emphasizes the importance of stylistic analysis in comprehensively uncovering the depth of meaning, coherence, and rhetorical power of Quranic discourse.